Novel Blood Biomarkers for an Earlier Diagnosis of Alzheimer's Disease: A Literature Review - Shiavax J. Rao; Andrew J. Boileau (University Library System, University of Pittsburgh, 2020)
Alzheimer's disease is a neurodegenerative condition associated with neurofibrillary tangles and cortical deposition of amyloid plaques. Clinical presentation of the disease involves manifestations such as memory loss, cognitive decline and dementia with some of the earliest reported deficits being episodic memory impairment and olfactory dysfunction. Current diagnostic approaches rely on autopsy characterization of gross brain pathology, or brain imaging of biomarkers late in the disease course. The aim of this literature review is to identify and compare novel blood-based biomarkers with the potential of making an earlier clinical diagnosis of Alzheimer's disease. Utilizing such techniques may allow for earlier therapeutic intervention, reduction of disability and enhancement of patients' quality of life. Literature review and analysis was performed by screening the PubMed database for relevant studies between July 1, 2014 and December 31, 2019. Sixteen studies were reviewed with biomarker candidates categorized under microRNAs (miRNAs), auto-antibodies, other blood-based proteins or circulating nucleic acids. Three biomarker candidates - serum neurofilament light chain, plasma ?-secretase 1 activity and a panel of three miRNAs (miR-135a/193b/384) - reported statistically significant differences in testing between patients and controls, with high discriminative potential and high statistical power. In conclusion, certain blood biomarkers have shown promising results with high sensitivity and specificity, high discriminative potential for Alzheimer's disease early in its progression, and statistically significant results in larger study samples. Utilization of such diagnostic biomarkers could increase the efficacy of making an earlier clinical diagnosis of Alzheimer's disease.